answersLogoWhite

0

Slope intercept form is y = mx + b. Point slope form is y - y1 = m(x - x1).

Here is an example of changing slope-intercept form to point-slope form: Change y = 3x + 2 to point slope form:

y = 3x + 2

Subtract 2 from each side:

y -2 = 3x

The equation y-2 = 3x is in point-slope form. It can be rewritten as

y-2 = 3(x-0), showing that the line passes through the point (0,2), but is doesn't need to be.

(The x1 and y1 represent one point on the line, it doesn't matter which one. Therefore, there are many different equations for the same line in point-slope form. For example, the equation y -2 = 3x is the same line as the equation y - 11 = 3(x - 3), which is the same line as the equation y + 4 = 3(x + 2).)

User Avatar

Wiki User

14y ago

Still curious? Ask our experts.

Chat with our AI personalities

JordanJordan
Looking for a career mentor? I've seen my fair share of shake-ups.
Chat with Jordan
RossRoss
Every question is just a happy little opportunity.
Chat with Ross
ReneRene
Change my mind. I dare you.
Chat with Rene

Add your answer:

Earn +20 pts
Q: How do you change slope-intercept form to point-slope form?
Write your answer...
Submit
Still have questions?
magnify glass
imp